U.S. National Parks and “The Tragedy of the Commons” - Séverine Wozniak; Arnaud Buchs (Revue de Géographie Alpine)
This paper aims at presenting the stakes related to the access to protected land in the United States and to its conservation, through the analysis of the professional practice of U.S. mountain guides. From a methodological standpoint, this research is based both on a theoretical analysis grounded in the field of environmental economics and on an empirical study. The authors’ starting point is Garrett Hardin’s paper, “The Tragedy of the Commons” (Science, 1968), even if it introduces some confusion on the notion of common goods. So as to avoid this confusion, the authors use two theoretical tools pertaining to a typology of common goods and the different property rights that can be applied in National Parks. Finally, they apply this framework to the observations made on the field in Colorado in July 2009.